Information, Mobile Telephony, and Traders' Search Behavior in Niger. (1st October 2014) - Tack, Jesse; Aker, Jenny C.
Abstract : Information and communications technologies have spread rapidly in developing countries. We investigate the impact of mobile phones on traders' search behavior in Niger by constructing a theoretical model of search in which traders engage in sequential search for the optimal sales price. Using a trader panel dataset spanning 2005–2007, we find empirical support for the model in that the duration of mobile phone coverage is associated with increased search activity. This effect evolves dynamically over time and is stronger for larger traders, who engage in arbitrage over longer distances. Results provide empirical evidence for the observed linkages between mobile telephony and price dispersion.